ASFS Presidential Address 2015, Chatham University: "Jainsa Khave Anna, Vainsa Hove Manna: As the Grains You Eat, So Will be the Mind". (2nd January 2016) - Ray, Krishnendu
Abstract: Productive new openings can be found in food studies through provincializing European and American conceptualizations of the aesthetics of good taste and the ethics of foodwork. The liberal arts can be reinvigorated for the twenty-first century by drawing on feminism and everyday Hinduism of care-work and devotion, in part by using the immigrant body not merely as an object of analysis but as a tool kit to open up the epistemological discussion on how we know what to do.